Clinical and Molecular Differentiation Between Malignant Rhabdoid Tumor of the Kidney and Normal Tissue: A Two-Case Report - Zhanghuang, Chenghao; Chen, Shuo; Li, Li; Yang, Zhen; Xie, Yucheng; Li, Jiwei; Tang, Haoyu; He, Xiaoli; Dong, Liuyi; Yan, Bing (Frontiers in Oncology, 2021)
Background: Malignant rhabdoid tumor of the kidney (MRTK) is a rare type of tumor that lacks typical clinical manifestations. Herein, we presented clinical data of 2 children with MRTK. In addition, we used a high-throughput RNA-sequencing (RNA-seq), GEO analysis, and KEGG signaling pathway analysis to analyze gene expression differences at the transcripts level between 2 patients with MRTK and 3 patients with non-tumor diseases without other symptoms Case report: Preoperative B ultrasound and CT examination in 2 cases suggested that nephroblastoma . Treated with radical nephrectomy after general anesthesia. After operation,MRTK diagnosis by pathological examination. Regular chemotherapy 7 courses(Child 1) and 12 courses(Child 2),followed up for 2 years(Child 1) and 3 years and 1 month(Child 2), without symptoms. RNA-seq results showed 2203 differential genes (DEGs) in the kidney tissue of children with MRTK compared to normal tissue (p <0.01). GO analysis suggested that most DEGs participate in protein binding. KEGG results showed that the DEGs were mainly involved in the PI3K-Akt signaling pathway and microRNA-related proteins. Conclusion: The PI3K-Akt signaling pathway and microRNA-related proteins as targets have extremely high potential value for the diagnosis and treatment of MRTK.